Creep Behaviour of Viscoelastic Polymer Materials - André, José Reinas (2016)
The non-linear creep compliance of a polypropylene (PP) was studied at 30, 40 and 50oC, for tensile stresses between 2 and 10 MPa. The model developed, which is based on physical mechanisms (at the molecular scale) responsible for the material’s behaviour, yields very good agreement with the experimental data and physically meaningful theoretical parameter values.